Effect of primary structural variation on cervid prion protein in flexibility, stability, and spontaneous misfolding propensity - Carlos M. Díaz-Domínguez; Hasier Eraña; Francesca Peccati; Enric Vidal; Jorge M. Charco; Cristina Sampedro-Torres-Quevedo; Miguel A. Pérez-Castro; Nuria L. Lorenzo; Samanta Giler; Glenn C. Telling; Mariví Geijo; Jesús R. Requena; et al. (Neurobiology of Disease)
Protein misfolding is central to numerous neurodegenerative disorders, collectively known as proteinopathies, which include Alzheimer's disease, Parkinson's disease, and prion diseases, among others. In many cases, specific polymorphisms of the proteins associated with these diseases influence their misfolding. However, the precise ways in which these polymorphisms affect protein integrity and how they contribute to misfolding propensity remain unclear. In the case of prion diseases, they are caused by prions or PrPSc, the misfolded isoforms of the cellular prion protein (PrPC). Chronic Wasting Disease (CWD) is a prion disease that affects cervids and can exhibit lymphotropic properties, making it the most widespread proteinopathy. For that reason, cervid PrPs and their polymorphisms have been extensively studied. To better understand the role of these polymorphisms, we analyzed 45 cervid PrP variants to assess their effects on flexibility, stability, and spontaneous misfolding propensity.The cervid variants were expressed as recombinant PrP in E. coli and were analyzed for thermal stability using circular dichroism. Additionally, the rec-PrPs served as substrates for Protein Misfolding Shaking Amplification (PMSA), enabling assessment of each variant's spontaneous misfolding propensity. This process led to the formation of bona fide prions, as confirmed by inoculation of one of the resulting conformers into transgenic mice expressing bank vole PrP. In parallel, molecular dynamics simulations were conducted to analyze the structural flexibility of the variants. While differences in protein flexibility were observed, no correlation was detected among flexibility, thermal stability, and the observed variable spontaneous misfolding propensity, suggesting that these properties are independent parameters.